Immigration, ethnicity, and class in American writing, 1830-1860 : reading the stranger - Buonomo, Leonardo (Fairleigh Dickinson University Press, 2014)
"This book examines the close relationship between the portrayal of foreigners and the delineation of culture and identity in antebellum American writing. Both literary and historical in its approach, this study shows how in a period marked by extensive immigration, heated debates on national and racial traits, and an unprecedented flowering in American letters, the responses of American authors to outsiders not only contain precious insights into 19th-century America's self-construction, but also serve to illuminate our own time's multicultural societies. The authors under consideration are alternately canonical (Emerson, Hawthorne, Melville), recently rediscovered (Kirkland), or simply neglected (Arthur). The texts analyzed cover such different genres as diaries, letters, newspapers, manuals, novels, stories, and poems"--